Pengaruh Kecerdasan Spiritual Terhadap Motivasi Belajar Peserta Didik Pada Mata Pelajaran IPA Terpadu - Nurmah; Jamilah, Jamilah; Ismail, Wahyuni (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
This study aimed to investigate the influence of spiritual intelligence on students' learning motivation in integrated science subjects at SMP Tahfidzul Qur'an Wahdah Islamiyah Makassar. This study used an associative investigation design to determine the relationship between variables. The study population comprised 40 students at SMP Tahfidzul Qur'an Wahdah Islamiyah Makassar. A Likert-scale questionnaire was employed as the research instrument, containing indicators of spiritual intelligence and learning motivation. Data collection involved descriptive and inferential analysis. The descriptive analysis revealed that students had an average level of spiritual intelligence of 72%, equivalent to 29%. Similar to the descriptive analysis, learning motivation was moderate, accounting for 70% of the 28 individuals. Based on the significance test of the inference analysis, it had a significance value of 0.001. Since the significance value is less than the probability value of 0.05 (0.001 < 0.05), H0 is rejected, whereas H1 is accepted. Thus, the researchers can conclude that spiritual intelligence influences students' learning motivation in the Integrated Science subject at SMP Tahfidzul Qur'an Wahdah Islamiyah Makassar.